Extraction and Evaluation of Software Components from Object-Oriented Artifacts - Rathee, Amit; Chhabra, Jitender Kumar (Informatica, 2021)
A doctoral thesis is summarized in this paper that focuses on strengthening the Component-Based Software Development (CBSD) approach by proposing an efficient approach for extracting and evaluating reusable software components from an Object Oriented (OO) software by utilizing its various artifacts. The carried out research work mainly consists of two main steps: (1) extracting a possible set of components by utilizing optimal software artifacts and clustering techniques; (2) identifying reusable components by evaluating the quality of different components using the proposed reusability metric suite. The carried out research work significantly helps in identifying and extracting the reusable components for the CBSD environment and the proposed metric suite helps in evaluating the quality of all components.